Dietary diversity associated with risk of cardiovascular diseases among community-dwelling older people: A national health examination survey from Thailand - Chalermsri, Chalobol; Ziaei, Shirin; Ekström, Eva-Charlotte; Muangpaisan, Weerasak; Aekplakorn, Wichai; Satheannopakao, Warapone; Rahman, Syed Moshfiqur (Frontiers in Nutrition, 2022)
Background: Cardiovascular diseases (CVD) are the common comorbidities in older people. Healthy diet is an essential strategy to alleviate the risk of developing CVD. Dietary diversity (DD) is an indicator of diet quality. Currently, limited research exists regarding DD and CVD in older people in developing countries, such as Thailand, despite rapid growth of older population. Therefore, this study aims to determine associations of DD with the risk of CVD and the cardiometabolic risk factors among Thai older people. Methods: This cross-sectional study used the sub-sample of the fifth Thai National Health Examination Survey conducted from 2013 to 2015. A total of 6,956 older people aged 60 years and older and no pre-existing CVD were included. Dietary diversity score (DDS) was assessed the consumption of eight food groups using food frequency questionnaires. Each food group was scored from 0 to 4. The DDS was calculated as the sum of the scores (0-32). The risk of CVD was calculated by using a Thai cardiovascular (CV) risk score. The cardiometabolic risk factors included hypertension, diabetes mellitus (DM), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglyceride (TG) levels. Data were adjusted for a complex survey design and analysed using linear and logistic regression models. Results: In the adjusted model, DDS had a significant negative association with log-Thai CV risk score, with adjusted β (95% CI) values of -0.01 (-0.01, -0.01). Regarding the cardiometabolic risk factors, DDS had a significant negative association with hypertension, DM and log-TG levels, with adjusted OR (95% CI) values of 0.97 (95% CI 0.97, 0.98) for hypertension, 0.94 (0.93, 0.95) for DM, and adjusted β (95% CI) values of -0.002 (-0.004, -0.001) for log-TG level. DDS was positively associated with TC and LDL-C, with adjusted β (95% CI) values of 0.59 (0.38, 0.80) for TC and 0.59 (0.38, 0.79) for LDL-C levels, while DDS was not associated with HDL-C level. Conclusion: Higher DD was associated with a lower risk of CVD among Thai older people. The nutritional policies or interventions should encourage a diverse food intake for the prevention of CVD in this population.